Solid Knowledge Management – The Ingredient Companies Need for Performance: A Romanian Insight - Victoria Stanciu; Andrei Tinca (Journal of Accounting and Management Information Systems (JAMIS), 2017)
The paper explores knowledge management (KM) through the accounting and auditing field, emphasizing the authors' research results designed to examine the Romanian firms' perspective on KM. The authors strive to understand how the audit firms manage their knowledge aiming at providing quality services with added value. The important changes in auditing and accounting standards and national regulations and the dynamic of the profession in the Big Data era determine the need of a continuous process of information gathering and storage next to the increase of accountants and auditors' expertise and skills. The investigation revealed an insufficient understanding of KM concept and lack of focus on KM process implementation, this being the consequence of the numerous small and medium accounting and auditing firms, limited investments in IT tools for audit and KM purposes and insufficient training on KM issues. The paper contributes to the KM and auditing literature by demonstrating the need to urgent the implementation of KM systems in Romanian audit firms and providing suggestions in this regard.
Keywords: M14; M41; M42; D83; 650; Knowledge management; accounting; auditing; organizational culture; performance